Karyotype analysis and chromosome banding of Upeneus moluccensis (Bleeker, 1855) from the north-eastern Mediterranean. Issue 2 (2nd April 2016) - Karahan, Arzu
Abstract: Chromosome number, morphology and location of the nucleolus organizer region (NOR) are useful cytological characters for taxonomic and evolutionary studies. The karyotype of Upeneus moluccensis from the north-eastern Mediterranean was investigated through conventional Giemsa staining, Ag-NOR staining, C-banding and GTG-banding techniques. The results showed 2 n = 44 (FN = 46), 2m + 2st + 40a chromosomes and four NORs. Two telomeric C-band regions were observed on a metacentric and subtelocentric chromosome pair. On the basis of the chromosome morphology, the GTG and C-banding pattern, it is hypothesized that Upeneus moluccensis is more primitive than the Mediterranean native fish species, Mullus barbatus and Mullus surmuletus . In this study, the cytogenetic characterization of U. moluccensis has been carried out for the first time.